PENAPISAN FITOKIMIA DAN ANTIBAKTERI EKSTRAK METANOL MANGROVE (Excoecaria agallocha) DARI MUARA SUNGAI PORONG - Asep Awaludin Prihanto; Muhamad Firdaus; Rahmi Nurdiani (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
The aims of this study were to screen phytochemical and antibacterial potency of methanol extract of Excoecaria agallocha. The phytochemical screening used qualitative analysis and the antibacterial assay determined by diffusion method. The results showed that extracts of leaf, flower, bark, stem and root of Excoecaria agallocha, respectively, contained alkaloid, steroid, flavonoid, tannin, terpenoid and saponin. Methanol extract of all part of Excoecaria agallocha, except the root, inhibited the growth of gram positive bacteria (Staphylococcus aureus ATCC 9144), Meanwhile, the leaf of Excoecaria agallocha extract not only inhibited the growth of gram positive bacteria (Staphylococcus aureus ATCC 9144) but also the growth of gram negative bacteria (Escherichia coli ATCC 8739).